Localized surface plasmon resonance of copper nanoparticles improves the performance of quasi-two-dimensional perovskite light-emitting diodes. (April 2021) - Jhuang, Lu-Syuan; Kumar, Gautham; Chen, Fang-Chung
Abstract: Plasmonic nanoparticles (NPs) based on noble metals are often used for improving the performance of optoelectronic devices. Widescale use of these nanostructures for commercial applications, however, has been hampered by their high material cost. Herein, we use copper (Cu), which is more abundant and low-cost, to synthesis NPs; the NPs are further capped with polyvinylpyrrolidone to improve their ambient stability. The as-prepared Cu NPs are incorporated into quasi-two-dimensional perovskite light-emitting diodes for increasing the device efficiencies. The luminous efficiency can be improved up to 115%. From the photoluminescent studies, we attribute the device enhancement to the plasmonic effects of Cu NPs. We anticipate that the cost-effective polymer-capped Cu NPs may trigger demand of plasmonic nanostructures for use in commercial optoelectronic devices. Graphical abstract: Image 1 Highlights: Cu NPs are not stable in the air. The NPs are protected by capping with polyvinylpyrrolidone. The NPs are applied onto the surface of PEDOT:PSS anode buffer layers. The efficiency of the perovskitelight-emitting diodes is improved by 115%. The improvement is attributed to the localized surface plasmon resonance of the Cu NPs.